Exacerbations in cystic fibrosis: 4 · Non-cystic fibrosis bronchiectasis. Issue 3 (28th February 2008) - Chang, A B; Bilton, D
Abstract : Bronchiectasis unrelated to cystic fibrosis (CF) is increasingly recognised as an important and major primary respiratory disease in developing countries. In affluent countries, bronchiectasis is also increasingly recognised in subsections of communities (such as indigenous peoples) as well as a co-existent disease/co-morbidity and disease modifier in respiratory diseases such as chronic obstructive pulmonary disease. The epidemiology, pathogenesis, prevention and management of exacerbations of non-CF bronchiectasis are reviewed. There are few data on all aspects of exacerbations in bronchiectasis. Some of the management issues are common to non-CF and CF bronchiectasis, but it would be unwise to extrapolate from CF studies to non-CF bronchiectasis. In some situations this may be harmful.